2018
DOI: 10.1002/adma.201706246
|View full text |Cite
|
Sign up to set email alerts
|

Long Electron–Hole Diffusion Length in High‐Quality Lead‐Free Double Perovskite Films

Abstract: Developing environmentally friendly perovskites has become important in solving the toxicity issue of lead-based perovskite solar cells. Here, the first double perovskite (Cs AgBiBr ) solar cells using the planar structure are demonstrated. The prepared Cs AgBiBr films are composed of high-crystal-quality grains with diameters equal to the film thickness, thus minimizing the grain boundary length and the carrier recombination. These high-quality double perovskite films show long electron-hole diffusion lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
263
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(285 citation statements)
references
References 31 publications
(29 reference statements)
15
263
0
Order By: Relevance
“…[55] Second, for B(III) cations, the transition metal cations with multiple oxidation states and/or partially occupied d or f orbitals are not desirable for designing photovoltaic absorbers, because they may introduce deep defect states and too localized band edges. Largesize single crystals, [155,[172][173][174] nanocrystals, [175][176][177][178] and highquality films [179][180][181][182] The element Au is half-colored because it exists only in the compounds A 2 Au 2 X 6 with A = Rb, Cs and X = Cl, Br, I. Most of the reported double perovskites are fluorides and chlorides, [158,159] which generally have too large bandgaps for photovoltaic applications.…”
Section: A 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…[55] Second, for B(III) cations, the transition metal cations with multiple oxidation states and/or partially occupied d or f orbitals are not desirable for designing photovoltaic absorbers, because they may introduce deep defect states and too localized band edges. Largesize single crystals, [155,[172][173][174] nanocrystals, [175][176][177][178] and highquality films [179][180][181][182] The element Au is half-colored because it exists only in the compounds A 2 Au 2 X 6 with A = Rb, Cs and X = Cl, Br, I. Most of the reported double perovskites are fluorides and chlorides, [158,159] which generally have too large bandgaps for photovoltaic applications.…”
Section: A 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 99%
“…The indirect bandgap is explained by the mismatch in angular momentum of the atomic orbitals of Ag and Bi that comprise the valence band top and the conduction band bottom. [179][180][181] Greul et al [179] first demonstrated the synthesis of Cs 2 Ag-BiBr 6 films and then used the films to fabricate solar cells in the regular mesoporous structure. Defect calculations showed that Bi vacancy and Ag-on-Bi antisite create deep states in the bandgap and thus should be carefully suppressed during the synthesis process for optimized optoelectronic properties.…”
Section: A 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…[119] However, the experimental results demonstrated that a lot of work was still to be done to ensure the reliability of this method. [78,79,118] The solution is then cooled to room temperature and deposited onto a charge-transport layer such as TiO 2 and SnO 2 by spin-coating. [120] Apart from the report by Greul et al in which Cs 2 AgBiBr 6 precursor was directly dissolved in dimethyl sulfoxide (DMSO) prior to device fabrication, [80] halide double perovskites of Cs 2 AgBiBr 6 are commonly prepared by an initial synthesis of corresponding single crystals, which are subsequently redissolved in organic solvents such as DMSO and dimethyl formamide (DMF) at elevated temperatures.…”
Section: Thin Film Preparationmentioning
confidence: 99%
“…A colorless solid, chloride double perovskite, Cs 2 NaBiCl 6 , has also been prepared. [78][79][80] This research area has blossomed owing to the numerous efforts made already to solve the issues of toxicity and stability in perovskite solar cells. [76,77] Notably, study interest has been moved to halide based double perovskites for potential PV application.…”
Section: Introductionmentioning
confidence: 99%